Design and investigation of negative capacitance–based core‐shell dopingless nanotube tunnel field‐effect transistor - Apoorva; Naveen Kumar; S. Intekhab Amin; Sunny Anand (IET Circuits, Devices and Systems)
Abstract Investigation and analysis of a ferroelectric material–based dopingless nanotube tunnel field‐effect transistor are conducted using a lead zirconate titanate (PZT) gate stack to induce negative capacitance in the device. Landau–Khalatnikov equations are used in deriving the parameter values of the ferroelectric material to ensure accurate results. The nanotube structure of the tunnel field‐effect transistor allows for better electrostatic control owing to its gate‐all‐around structure. Incorporation of negative capacitance further reduces the voltage supply requirement and power consumption of the structure while simultaneously improving switching. In addition, the device is studied for varying thicknesses of the dielectric PZT material. The threshold voltage of the device under study was calculated as 0.281 V, and the average subthreshold slope of the device was reduced to 18.271 mV/decade, far below the thermionic limit of 60 mV/decade.